2016
DOI: 10.4238/gmr.15038582
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of polymorphisms in miR146a, miR196a, and miR499 to the development of hepatocellular carcinoma

Abstract: ABSTRACT. Hepatocellular carcinoma is one of the most common malignant tumors worldwide; it is estimated that there were 782,000 new cases in 2012. MicroRNAs (miRNAs) play an important role in carcinogenesis by regulating oncogenes and tumor suppressors. We investigated the role of miR-146a, miR-196a2, and miR-499 polymorphisms in the risk of hepatocellular carcinoma in a Chinese population. Hepatocellular carcinoma patients (175) and healthy controls (302) were recruited between April 2013 and March 2015. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…However, this study did not show genetic association of rs3746444 polymorphism with periodontitis. These results are similar to studies conducted in Chinese population, showing lack of association of this polymorphism with hepatocellular carcinoma and ischaemic stroke, though the miR‐499 was earlier reported to be involved in cancer and heart diseases (Zhang, Hao, Zhang, Dai, & Zhang, 2016; Zhu, Hou, Ma, Yang, & Pan, 2018). Thus, finding out the association of miR‐499 polymorphisms with periodontitis opens up the possibility of understanding the aetiopathogenesis of inflammatory disease like periodontitis, formulating proper treatment modalities and preventive measures.…”
Section: Discussionsupporting
confidence: 90%
“…However, this study did not show genetic association of rs3746444 polymorphism with periodontitis. These results are similar to studies conducted in Chinese population, showing lack of association of this polymorphism with hepatocellular carcinoma and ischaemic stroke, though the miR‐499 was earlier reported to be involved in cancer and heart diseases (Zhang, Hao, Zhang, Dai, & Zhang, 2016; Zhu, Hou, Ma, Yang, & Pan, 2018). Thus, finding out the association of miR‐499 polymorphisms with periodontitis opens up the possibility of understanding the aetiopathogenesis of inflammatory disease like periodontitis, formulating proper treatment modalities and preventive measures.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 65 studies, sample sizes ranged from 175 to 3,585, and publication year ranged from 2009 to 2017. In total, there were 2 acute lymphoblastic leukemia studies (Gutierrez-Camino et al, 2014 ; Hasani et al, 2014 ), 10 breast cancer studies (Hu et al, 2009 ; Catucci et al, 2010 ; Alshatwi et al, 2012 ; Bansal et al, 2014 ; Omrani et al, 2014 ; He et al, 2015 ; Qi et al, 2015 ; Dai et al, 2016 ; Afsharzadeh et al, 2017 ), 3 bladder cancer studies (Mittal et al, 2011 ; Deng et al, 2015 ; Wang et al, 2016 ), 5 colorectal cancer studies (Min et al, 2012 ; Vinci et al, 2013 ; Hu et al, 2014 ; Dikaiakos et al, 2015 ; Ying et al, 2016 ), 2 cervical squamous cell carcinoma studies (Zhou et al, 2011 ; Srivastava et al, 2017 ), 3 esophageal cancer studies (Umar et al, 2013 ; Wei et al, 2013 ; Shen et al, 2016 ), 7 gastric cancer studies (Okubo et al, 2010 ; Ahn et al, 2013 ; Wu et al, 2013 ; Pu et al, 2014 ; Cai et al, 2015 ; Poltronieri-Oliveira et al, 2017 ; Rogoveanu et al, 2017 ), 17 hepatocellular carcinoma studies (Akkiz et al, 2011 ; Kim et al, 2012 ; Xiang et al, 2012 ; Zhou et al, 2012 , 2014 ; Shan et al, 2013 ; Zou and Zhao, 2013 ; Chu et al, 2014 ; Hao et al, 2014 ; Kou et al, 2014 ; Ma et al, 2014 ; Qi et al, 2014 ; Wang et al, 2014 ; Li D. et al, 2015 ; Li X. et al, 2015 ; Yan et al, 2015 ; Zhang et al, 2016 ), 4 lung cancer studies (Tian et al, 2009 ; Vinci et al, 2011 ; Li D. et al, 2016 ), 2 oral squamous cell cancer studies (Hou et al, …”
Section: Resultsmentioning
confidence: 99%
“…Wang et al ( 2014 ) found that miR-499A>G polymorphism is associated with an increased risk of hepatocellular carcinoma in Chinese individuals. However, Zhang et al ( 2016 ) suggested that there is no association between miR-499 variant and the risk of hepatocellular carcinoma in the co-dominant, dominant, and recessive models. These two articles similarly focus on hepatocellular carcinoma, but it led to very different results.…”
Section: Introductionmentioning
confidence: 99%
“…When the source of heterogeneity was analyzed, we found that high-quality score (≥7.0), small sample size (<1000 subjects), CRC, HCC, GC, ESCC, Asians and hospital-based study subgroups increased it greatly. Additionally, in dominant model (Figure 2), Galbraith radial plot and the forest plot identified eleven outliers (Chae et al 2013;Dikaiakos et al 2015;Duan Lei 2017;Guo et al 2010;Kupcinskas et al 2014a;Li et al 2015;Lv et al 2013;Ma 2012;Srivastava et al 2010;Zhang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used Galbraith radial plot to determine the heterogeneity ( Figure 5). Among the eligible studies, eleven outliers (Chae et al 2013;Dikaiakos et al 2015;Duan Lei 2017;Guo et al 2010;Kupcinskas et al 2014a;Li et al 2015;Lv et al 2013;Ma 2012;Srivastava et al 2010;Zhang et al 2016) were found, which contributed to the main heterogeneity.…”
Section: Heterogeneitymentioning
confidence: 99%